BUDAYA INTERNET: PERKEMBANGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENDUKUNG PENGGUNAAN MEDIA DI MASYARAKAT - Kristiyono, Jokhanan (Institute of Research and Community Outreach - Petra Christian University, 2015)
The emergence of The Internet as a new communication medium has been associated with conflicting claims about the rise of new pattern of social interaction. The idea of virtual communities advanced by the pioneers of social interaction on the Internet. High Internet usage can eventually lead to new social problems, the example problem is excessive use of electronic communication to personal that is reducing the forms of interaction between personal communication, even very unusual we find out personal information to someone published in general use social media status even tough that is very personal problems. Conclusion from the research are: First, the use of Internet-based media in excess will cause a lot of problems ranging from addiction, behavioral changes to crimes cyber world. Second, the Internet culture developed at this time because there is a synergy created from four cultures in it, namely, Technocratic, Hacker, Virtual Communitarians, and Entrepreneurial. Third, Media Education or training in using the media becomes very important to foster media literacy.